Sustaining the cultural vitality of urban public markets: A case study of Pasar Payang, Malaysia - Zakariya, Khalilah; Kamaruddin, Zumahiran; Harun, Nor Zalina (ArchNet-IJAR, 2016)
The development of a public market in the city planning is pivotal in supporting the growth of the local economy. The market is also a place where the culture of the locals evolves daily. However, the unique qualities of the market are vulnerable to the redevelopment process. This study examines the cultural aspects of Pasar Payang in Terengganu, Malaysia, as one of the well-known markets among the locals and the tourists, which will soon be redeveloped. The aim of this paper is to identify the tangible and intangible qualities of the market, so that it can sustain its cultural qualities in the future. The methods adopted for this study comprise of conducting a survey among 497 visitors, and semi-structured interviews among 19 market vendors. The findings reveal that the cultural vitality of the market can be sustained by strengthening its local identity through its products and culture, providing spaces that can facilitate tourist activities and cultural participation, and enhancing the development of the local businesses.